COMPUTER ANALYSIS OF THE GMAW AND GMAW-CW WELDING THERMAL CYCLES - Mendonça, E. A. M.; Braga, E. M.; Ferreira, A. S. A.; Maciel, R. R.; Cabral, T. S.; Lopes, J. T. B. (Revista de Engenharia Térmica, 2015)
A novel process of welding GMAW-CW (Gas Metal Arc Welding-Cold Wire) had been developed with it resemblance to the GMAW (Gas Metal Arc Welding), the GMAW-CW has an additional wire fed into de weld pool, allowing better deposition rates, while maintaining weld characteristics. However, there is a more complex situation related to the HAZ (Heat Affected Zone) and weld geometry prediction than the GMAW conventional. The welding energy is a high metallurgical important parameter because together with the geometric characteristics of the gasket and the preheat level is decisive in thermal cycles imposed to the material, and therefore in the possible microstructural transformations and behavior of the joint. The behavior of representative curves of thermal cycling reflects important aspects regarding the conditions used in welding. Usually such factors as the type of process, use or non- pre or post- heating, heat input, multipass welding, are able to establish differences in the form of a heat cycle curve. In this work, it was applied the dual ellipsoidal model of heat input, adapted to the GMAW-CW and compared to the same model over the GMAW, using existing experimental data and predicting the HAZ dimensions in function of weld and welding parameters. The results found had less than 10% error from experimental data in a more refined version of the model, whereas the difficulties to predict cold wire addition influences were not trivial.